Clinical practice guidelines: management of Obstructive Sleep Apnoea - Mohamed, Ahmad Fariz; Piper, Amanda J; Nathan, Anna Marie; Teng, Arthur; Yoon, Audrey; Cherng, Chan Giin; Tanikawa, Chihiro; Ibrahim, Haiza; Wen, Han Yung; Mohamad, Hazama; Kiau, Ho Bee; Kassim, Ismail; et al. (Malaysian Health Technology Assessment Section (MaHTAS), Medical Development Division, Ministry of Health Malaysia, 2023)
The objectives of the CPG are to provide evidence-based recommendations on the management of OSA in adults and children based on the following aspects: a. screening b. diagnosis and assessments c. treatment options d. monitoring and follow-up e. special groups This document is intended to guide healthcare professionals and relevant stakeholders in primary and secondary/tertiary care of the management of OSA including: • doctors and dental surgeons • allied health professionals • trainees and medical students • patients and their advocates • professional societies